Evaluation of Occupational Health and Safety System: A Case Study of Hepatitis B Due to Needle Stick Injury in a Sanitarian - Stellon Salim; Dewi Sumaryani Soemarko (The Indonesian Journal of Community and Occupational Medicine, 2025)
Background: Work-related Hepatitis B is a significant health issue among healthcare workers, especially those at high risk of needle stick injuries (NSI). Needle stick injuries can act as a transmission route for the Hepatitis B virus, which, if not adequately managed, may lead to serious complications. Evaluating the Hospital Occupational Health and Safety System (OHSS) is crucial to prevent similar incidents. This study aims to evaluate the OHSS system in a hospital for preventing workplace injuries and to analyze a case of Hepatitis B resulting from a needle stick injury in a sanitarian.Case presentation: A 37-year-old male sanitarian was diagnosed with Hepatitis B following a Medical Check-Up that revealed reactive HBsAg without clinical symptoms. The incident occurred in April 2021 when the patient was pricked by a used needle while handling medical waste without using appropriate personal protective equipment (PPE) and without reporting the incident to the hospital’s occupational health unit. The patient had no history of Hepatitis B vaccination and was previously declared HBsAg negative during a 2020 medical check-up. Based on the analysis using the Seven Steps of Occupational Diagnosis, the incident was categorized as an Occupational Disease due to the failure of the OHSS system in preventing infections.Methods: This case report draws on clinical observations and a retrospective review of patient records, using the Seven Steps of Occupational Diagnosis framework to determine causal factors. Workplace safety protocols, including PPE availability and incident reporting processes, were assessed. The patient provided informed consent for the use of their data, with all identifying details removed to maintain confidentiality.Conclusion: Based on the evaluation using the managerial approach of OHSS, the Hepatitis B case in this sanitarian can be categorized as a work-related disease. The needle stick injury leading to Hepatitis B virus transmission highlights deficiencies in implementing workplace safety systems in the hospital. This study emphasizes the importance of strengthening the OHSS system through regular training, adequate PPE provision, improved Standard Operating Procedures (SOPs), and continuous monitoring to prevent similar incidents.